2005
DOI: 10.1302/0301-620x.87b3.15338
|View full text |Cite
|
Sign up to set email alerts
|

Epidural steroid injection for nerve root compression

Abstract: We have assessed whether an epidural steroid injection is effective in the treatment of symptoms due to compression of a nerve root in the lumbar spine by carrying out a prospective, randomised, controlled trial in which patients received either an epidural steroid injection or an intramuscular injection of local anaesthetic and steroid. We assessed a total of 93 patients according to the Oxford pain chart and the Oswestry disability index and followed up for a minimum of two years. All the patients had been c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
121
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(126 citation statements)
references
References 20 publications
2
121
0
2
Order By: Relevance
“…Two studies included patients who had previously received an epidural for their current episode, but this information was not reported for most studies. Three studies 94,156,169 included patients who had had previous disc surgery, one of which 169 did not report data on global effect, pain or CSOMs. (One study 95 compared the use of epidural with disc surgery.)…”
Section: Summary Of Study Participants For Epidural/intradiscal Injecmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies included patients who had previously received an epidural for their current episode, but this information was not reported for most studies. Three studies 94,156,169 included patients who had had previous disc surgery, one of which 169 did not report data on global effect, pain or CSOMs. (One study 95 compared the use of epidural with disc surgery.)…”
Section: Summary Of Study Participants For Epidural/intradiscal Injecmentioning
confidence: 99%
“…(One study 95 compared the use of epidural with disc surgery.) Two studies 156,166 (comparator included non-opioids) included some patients with spinal stenosis and one study 94 (epidural vs disc surgery) included patients with sequestered discs. Summary of study design and quality for epidural/intradiscal injection studies Summary information on study details is presented in Table 19, excluding studies 146,161,164,169,172 that did not report outcome data for global effect, pain intensity or CSOMs.…”
Section: Summary Of Study Participants For Epidural/intradiscal Injecmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it was found that there is a requirement of more randomized controlled studies for the evaluation of the impact of the associated factors such as lengths of treatment, wavelengths and dosage [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study was conducted on 92 patients with a 16 gauge tuohy needle. The injection was administered at the specific interval near the affected nerve root [11]. When the needle touched lamina, it was pulled back a little and one group of patients received a steroid injectate into muscle tissue whereas the other group received a steroid into the epidural space.…”
Section: L4-l5 N (%)mentioning
confidence: 99%